ADVANCED PLANNING SYSTEMS (APS) FOR SUPPLY CHAIN PLANNING: A CASE STUDY IN DAIRY INDUSTRY - Zago, Cecília Farid; Mesquita, Marco Aurélio de (Brazilian Journal of Operations & Production Management, 2015)
This paper discusses which benefits the use of APS may bring to the S&OP, and the critical factors for the successful implementation. A case study was conducted in a major dairy company in the Brazilian food industry. Positioned in an environment of high market competition and narrow profit margins, the company strives for operational excellence, aimed at inventory reduction and increased service level. This supply chain includes several plants and has recently been through the deployment of an APS to support its S&OP process. The research has identified the main benefits of the APS: greater confidence and accuracy in planning, and better balancing of inventory throughout the supply chain. The deployment project went through specific difficulties that delayed its schedule. The study reinforces the importance of fully support from senior managers and the commitment of the planning staff to meet the challenges of customization and integration of the new system.